The collapse of freedom of expression: reconstructing the ancient roots of modern liberty - Pujol, Jordi (Catholic ideas for a secular world, 2023)
"This book offers a holistic account of the problems posed by freedom of expression in our current times and offers corrective measures to allow for a more genuine exchange of ideas within the global society. The topic of free speech is rarely addressed from a historical, philosophical, or theological perspective. In The Collapse of Freedom of Expression, Jordi Pujol explores the modern concept of the freedom of expression based on the European Enlightenment, and the deficiencies inherent in this framework. Modernity has disregarded the traditional roots of the freedom of expression drawn from Christianity, Greek philosophy, and Roman law, which has left the door open to the various forms of abuse, censorship, and restrictions seen in contemporary public discourse. Pujol proposes that we rebuild the foundations of the freedom of expression by returning to older traditions and incorporating both the field of pragmatics of language and theological and ethical concepts on human intentionality as new, complementary disciplines. Pujol examines emblematic cases such as Charlie Hebdo, free speech on campus, and online content moderation to elaborate on the tensions that arise within the modern concept of freedom of expression. The book explores the main criticisms of the contemporary liberal tradition by communitarians, libertarians, feminists, and critical race theorists, and analyzes the gaps and contradictions within these traditions. Pujol ultimately offers a reconstruction project that involves bridging the chasm between the secular and the sacred and recognizing that religion is a font of meaning for millions of people, and as such has an inescapable place in the construction of a pluralist public sphere"--